Analisis Kualitas Beton Dengan Memperhatikan Pasir: Perbandingan Pasir Dicuci dan Pasir Tidak Dicuci Pada Kuat Tekan Beton - Saputra, Achmad Faisal; Jamaludin, Jamaludin; Zain, Alfath (Universitas Batanghari Jambi, 2024)
Concrete is a building material that is widely used in construction. Currently, various methods continue to be developed with the aim of increasing the strength of concrete. Concrete is obtained by mixing fine aggregate, coarse aggregate, directly adding cement paste and water. Sand is a fine aggregate material that is most widely used in the construction sector, from the bottom of the building to the top of the building, such as in making roads, embankments, buildings or as a mortar for concrete mixtures. Sand in concrete greatly influences one of the materials used, namely Mount Sugih sand which is located in Gunung Sugih sub-district, Central Lampung district, Lampung province, where sand from Mount Sugih is famous for its quality compared to sand in every area of Lampung. This research aims to determine the compressive strength using Mount Sugih sand to compare washed and unwashed sand. The test object used is a cylinder with a diameter of 15 mm and a height of 30 mm. The concrete tested was 3, 7 and 21 days old and converted 28 days from a total of 8 test objects. Examination of the mud content of unwashed sand was 7.93% and washed sand was 3.06%. From the results of the tests that have been carried out, the results from washed sand were 197,625 kg/cm2 for 3 days, 263,490 kg/cm2 for 7 days, 265,093 kg/cm2 for 7 days, 21 days 241,117 kg/cm2 for unwashed sand results for 3 days 194,947 kg/cm2, 7 days 210,809 kg/cm2, 7 days 187,140 kg/cm2, 21 days 190,240 kg/cm2 from the results obtained, the washed Sugih mountain sand experienced a very good increase and the unwashed Sugih mountain sand experienced a decrease.